Analisis Sumber Daya Manusia Dalam Usaha Kecil Pertanian - Mulasih, Siti; Sukardi, Sukardi; Noor, Muhamad Arief; Tohiroh, Tohiroh (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study aims to analyze human resources in small agricultural enterprises, focusing on identifying factors that influence productivity and business sustainability. The research subjects are small-scale farmers in the Garuda 12 Women's Farming Group in Cipayung, Ciputat, South Tangerang, who own less than 200 m² of agricultural land. The research method used is a qualitative approach involving in-depth interviews and participatory observations. Data were collected from 30 members of the Garuda 12 Women's Farming Group in Cipayung, Ciputat, South Tangerang, using purposive sampling to ensure the selected respondents have high relevance to the research topic. The collected data were analyzed using thematic analysis to identify main themes related to human resources. The results indicate that technical skills, access to training, and time management are key factors influencing the productivity of small-scale farmers. Additionally, support from government and non-governmental organizations in the form of extension services and technical assistance also plays a significant role in improving human resource quality. However, limited capital and access to modern technology remain major challenges. The implications of this research suggest that enhancing human resource quality can be achieved through continuous training programs and better access to resources and technology. This study contributes to the understanding of the importance of human resource development in small agricultural enterprises and can serve as a basis for designing more effective policies to support small-scale farmers